A novel framework for improvement of road accidents considering decision-making styles of drivers in a large metropolitan area. (February 2016) - Azadeh, Ali; Zarrin, Mansour; Hamid, Mehdi
Highlights: The objective of this paper is modeling and improvement of road accidents factors. Injury severity and decision-making styles of drivers are considered. A novel framework is proposed based on DEA and statistical methods. The actual data of more than 500 drivers in Tehran, Iran is used. Results indicate that flexible decision style is dominant for all accident injuries. Abstract: Road accidents can be caused by different factors such as human factors. Quality of the decision-making process of drivers could have a considerable impact on preventing disasters. The main objective of this study is the analysis of factors affecting road accidents by considering the severity of accidents and decision-making styles of drivers. To this end, a novel framework is proposed based on data envelopment analysis (DEA) and statistical methods (SMs) to assess the factors affecting road accidents. In this study, for the first time, dominant decision-making styles of drivers with respect to severity of injuries are identified. To show the applicability of the proposed framework, this research employs actual data of more than 500 samples in Tehran, Iran. The empirical results indicate that the flexible decision style is the dominant style for both minor and severe levels of accident injuries.